1952
DOI: 10.1063/1.1702324
|View full text |Cite
|
Sign up to set email alerts
|

Production of Monochromatic X-Radiation for Microradiography by Excitation of Fluorescent Characteristic Radiation

Abstract: ENERGY IN COPPER INTRODUCED BY COLD WORK 881 error in E to be of the order of 10 percent. It can be seen from these curves that this is so and that in the first run the release of latent energy begins at a temperature of between 100° and 125°C and is practically finished at a temperature of 250°C. As expected, the spread of the points becomes larger as the temperature increases. E, which is obtained as a simple average of the values of H(T), above 250°C, is given in Table 3 together with the value W. The last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1953
1953
1976
1976

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Monochromatic jluorescent X-ray beams were obtained from pure metal secondary targets made of silver, samarium, t'antalum and lead respectively (Rogers 1952) and placed in the primary x-ray beam from a 220 kv GE Maximar Unit. The K-emission weighted mean energies were 2 2 , 43, 61 and 74 kev respectively.…”
Section: No Fading Has Been Observedmentioning
confidence: 99%
“…Monochromatic jluorescent X-ray beams were obtained from pure metal secondary targets made of silver, samarium, t'antalum and lead respectively (Rogers 1952) and placed in the primary x-ray beam from a 220 kv GE Maximar Unit. The K-emission weighted mean energies were 2 2 , 43, 61 and 74 kev respectively.…”
Section: No Fading Has Been Observedmentioning
confidence: 99%
“…) and that of cobalt (1.79 A), were used to determine iron (Kabsorption edge, 1.74 A.). Rogers (110,111) has demonstrated that newly developed beryllium-window x-ray tubes provide, beams of such high intensityas to increase the attractiveness of the foregoing scheme for producing monochromatic x-ray-s. Splettstosser and Seemann (117,118) independentlyaccomplished the same result, as their published microradiographs show.…”
Section: X-ray Absorptionmentioning
confidence: 99%
“…K-fluorescent x rays excited in a secondary target by photons from the primary target of an x-ray tube have been used to obtain monoenergetic sources in the 1-to 100-keV energy range. ''^ Fluorescent sources, which have been used for microradiography of histologic sections 4 and for metallurgical microradiography,' have found widespread use in energy response measurements of radiation detectors*' 1 ' 1 and as a method of elemental analysis. 11 The radiation emitted by the secondary target consists not only of K-fluore3cent x rays but also includes the scattered bremsstrahlung contaminant.…”
Section: Introductionmentioning
confidence: 99%